Meningkatkan Kesadaran Hak Kewajiban Kehidupan Bermasyarakat Melalui Implementasi Pendidikan Kewarganegaraan - Ajeng April Setyaningrum; Irdina Qurrotul Aini (CV. KAMPUS AKADEMIK PUBLISING, 2026)
. This study underscores the significance of Civic Education (PKn) in strengthening citizens’ understanding of the balance between rights and responsibilities within the spheres of society, nation, and state. Rights are viewed as entitlements to be received, while responsibilities are obligations that must be fulfilled, and the harmony between the two is essential for sustaining democratic life as mandated by the 1945 Constitution. The research aims to examine the strategic role of Civic Education in nurturing democratic awareness and to identify barriers that hinder its effective practice. Employing a systematic literature review, the study synthesizes insights from twenty scholarly articles published between 2020 and 2025. The findings reveal that although Civic Education serves as a vital medium for instilling democratic values, its implementation continues to face challenges such as limited legal awareness, unequal access to education, and corruption that weakens civic integrity. The implications highlight the need for Civic Education to be delivered in a transformative and context-sensitive manner, utilizing active, adaptive, and participatory approaches. Through such methods, Civic Education is expected to cultivate responsible citizens who critically engage in democratic processes, uphold the balance between claiming rights and fulfilling obligations, and contribute to the sustainability of democracy in Indonesia.